The effects of planning on second language (L2) learners’ narrative oral production / Guo Zhonglan - Guo, Zhonglan (2014)
Recently, researches concerning task planning and its effects on second language (L2) learners’ speaking performance have demonstrated that planning can generally enhance learners’ speaking performance (Abdi, Eslami & Zahedi, 2012; Ahangari & Abdi, 2011; Bagheri & Hamrang, 2013; Crookes, 1989; Ellis, 1987; Mehnert, 1998; Mehrang & Rahimpour, 2010; Ortega, 1995; Ortega 1999; Rouhi & Marefat, 2006; Yuan & Ellis, 2003). However, in terms of pre-task planning and within task planning, there are no conclusive findings on which type of planning can benefit more to L2 learners’ speaking performance. Furthermore, few studies have explored the planning effects of pre-task planning plus within task planning as suggested by Yuan and Ellis (2003). Additionally, previous studies investigated learners’ planning process mainly from the perspective of the planning strategies that learners used. Few have studied learners’ planning process from the perspective of Levelt’s (1989) Model of Speech Production which explains how speaking takes place and where planning occurs during speaking and how planning can influence speech production, with the exception of Yuan and Ellis (2003). Nevertheless, Yuan and Ellis (2003) theoretically analyzed learners’ planning process. They did not collect data to analyze how learners approached the task. The present study attempted to fill the gaps stated above and explored learners’ planning process practically. This study utilized a between-subject experimental design. The participants in this study were randomly assigned to 4 groups, including 3 experimental groups and 1 control group. They were required to perform a narrative task under 4 conditions: pre-task planning, within task planning, pre-task planning plus within task planning and no planning. To investigate the planning effects, the participants’ speech was analyzed in terms of accuracy, complexity and fluency. To understand the learners’ planning process, information from post-task questionnaire was elicited and analyzed qualitatively based on Levelt’s (1989) speech production model. The results showed that pre-task planning can contribute more to learners’ L2 speaking performance than within task planning in general. Moreover, pre-task planning plus within task planning can positively influence learners’ speaking performance but there is no significant difference in its planning effects compared with pre-task planning and within task planning. These findings infer that learners’ speaking performance could be significantly enhanced when learners are well-equipped with explicit knowledge and are given time to plan under guidance. In addition, the results of the post-task questionnaire demonstrated that learners actually experienced the stages of Levelt’s (1989) Model of Speech Production. This finding strengthens Levelt’s (1989) theory. Key words: planning effects speaking L2 narrative